2021
DOI: 10.1002/jor.24970
|View full text |Cite
|
Sign up to set email alerts
|

Using area and volume measurement via weightbearing CT to detect Lisfranc instability

Abstract: Weightbearing CT (WBCT) allows evaluation of the Lisfranc joint under physiologic load. We compared the diagnostic sensitivities of one-dimensional (1D) distance, two-dimensional (2D) area, and three-dimensional (3D) volumetric measurement of the injured Lisfranc joint complex (tarsometatarsal, intertarsal, and intermetatarsal) on WBCT among patients with surgically-confirmed Lisfranc instability. The experimental group comprised of 14 patients having unilateral Lisfranc instability requiring operative fixa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…While the Listract test produced a nearly perfect ICC (97%) and it showed to increase in the sensitivity and specificity of both radiographic diastasis and area measurements, the need to reassess the cutoff values for both of these radiographic measurements seems inevitable. The interobserver agreement was moderate and good for diastasis and area measurement, respectively; however, previous reports using 3D weight-bearing CT scans have shown an ICC of >0.96 using 3D volume measurement for this non-invasive imaging method 10,[16][17][18] (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…While the Listract test produced a nearly perfect ICC (97%) and it showed to increase in the sensitivity and specificity of both radiographic diastasis and area measurements, the need to reassess the cutoff values for both of these radiographic measurements seems inevitable. The interobserver agreement was moderate and good for diastasis and area measurement, respectively; however, previous reports using 3D weight-bearing CT scans have shown an ICC of >0.96 using 3D volume measurement for this non-invasive imaging method 10,[16][17][18] (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 79%
“…Despite various imaging methods, intraoperative examination is the gold standard for confirmation of the diagnosis. 9,10 However, the intraoperative stress examination of the Lisfranc joint by applying a distraction force is not standardized and not a reproducible method. 11 Surgeons apply various amounts of force on the joint to confirm the diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the case of a far distal fracture. A combination with area and volume measurements could possibly reduce a larger error [ 27 ] and could be investigated in a further study. Furthermore, information about the medical history of the cadavers was limited.…”
Section: Discussionmentioning
confidence: 99%
“…9 Weightbearing CT (WBCT) affords a 3-dimensional (3D) view of the midfoot under physiologic load while also affording a contralateral comparison. 1,23 In a recent study, although suffering from a small population, WBCT modality showed a sensitivity of up to 92.3% and specificity of up to 97.7% in the detection of subtle Lisfranc instability. 1 Nonetheless, WBCT remains unavailable at many clinical sites.…”
Section: Introductionmentioning
confidence: 96%